κ-Opioid Agonist Modulation of [(3)H]Thymidine Incorporation into DNA: Evidence for the Involvement of Pertussis Toxin-Sensitive G Protein-Coupled Phosphoinositide Turnover - Barg, Jacob (1993)
A body of evidence has indicated that μ-opioid agonists can inhibit DNA synthesis in developing brain. We now report that κ-selective opioid agonists (U69593 and U50488) modulate [(3)H]thymidine incorporation into DNA in fetal rat brain cell aggregates in a dose- and developmental stage-dependent manner, κ agonists decreased thymidine incorporation by 35% in cultures grown for 7 days, and this process was reversed by the κ-selective antagonist, norbinaltorphimine, whereas in 21-day brain cell aggregates a 3.5-fold increase was evident. Cell labeling by [(3)H]thymidine was also inhibited by the κ-opioid agonist as shown by autoradiography. In addition, U69593 reduced basal rates of phosphoinositide formation in 7-day cultures and elevated it in 21-day cultures. Control levels were restored by norbinaltorphimine. Pertussis toxin blocked U69593-mediated inhibition of DNA synthesis. The action of κ agonists on thymidine incorporation in the presence of chelerythrine, a protein kinase C (PKC) inhibitor, or in combination with LiCl, a noncompetitive inhibitor of inositol phosphatase, was attenuated in both 7- and 21-day cultures. These results suggest that κ agonists may inhibit DNA synthesis via the phosphoinositide system with a pertussis toxin-sensitive G protein as transducer. In mixed glial cell aggregates, U50488 increased thymidine incorporation into DNA 3.1-fold, and this stimulation was reversed by the opioid antagonist naltrexone.